New Dimensions of Service Offshoring in World Trade - Marc Atkins; Bernard Michael Gilroy; Volker Seiler (Intereconomics, 2019)
This paper discusses the growing dimensions of the offshoring of service activities both in manufacturing and service industries. Trade in Value-Added data implies a great potential of service offshoring for global welfare, however, the negative effects have to be balanced by appropriate institutions in domestic and foreign countries.
Keywords: 330